(untitled) (Cadernos de Sociomuseologia, 2018)
This thesis entitled “The poetics of existence on the margins: paths of a museologist-poet through the artistic circuits of African Lisbon” presents the itineraries trekked to know what contemporary African art is presented in the art galleries of the Portuguese capital. I believe that science must be done with honesty, humanity and social responsibility. That is why everything that is written here is the result of my work in the intense exercise of thinking and writing in verbal and silent dialogues with other people, texts and images. In Lisbon, there is an interest in contemporary African artistic productions in the field of visual arts, by academics, curators and gallerists, but these artistic works are still restricted to the niche of art galleries with their select audience. The colonial remains traverse what is seen and what is consumed of contemporary African art, often avoiding the racism and xenophobia present in Portuguese society. In this academic-scientific writing, I did not extricate myself as a person-researcher and transformed my experiences into knowledge. I went beyond a quantitative sampling of works in the white, galeristic cube. I got caught up in the urban social fabric, unveiling Lisbon from my look of black, foreign and diasporic woman at the Atlantic crossroads. Keywords: Contemporary African Art, Atlantic, Crossroads, Art Galleries, Lisbon.